Composites Based on Polypropylene and Talc: Processing Procedure and Prediction Behavior by Using Mathematical Models. (1st November 2018) - Racca, Laiza Marinho; Pacheco, Elen Beatriz Acordi Vasques; Bertolino, Luiz Carlos; Campos, Cristiane Xavier da Silva; Andrade, Monica Calixto de; de Sousa, Ana Maria Furtado; Silva, Ana Lúcia Nazareth da
Abstract : iPP/Talc composites were produced, with different methods of filler addition in iPP matrix. Two different grades of Talc were used for comparison. The tensile tests results showed that talc particles promoted an improvement in composite rigidity, indicating the reinforcing effect of the talc particles in the iPP matrix. However, PP/talc-based composites that were prepared from a masterbatch and with talc grade with smaller particle size showed a better efficiency on dispersion/distribution of particle filler on the thermoplastic matrix, resulting in an improvement in Young's modulus property, even with higher filler contents. SEM analyses evaluated the composite morphologies and different mathematical models were used as a tool on prediction of mechanical behaviour of the materials. It was observed that the results of Young's modulus of the composites can be adjusted by different models, depending on the talc characteristics and the mixing procedure used.